Recognizing the overlooked: rethinking autism spectrum disorder symptom presentation in girls - Mete Yeşil, Ayşe; İskender, H. Ceren; Cihan Çam, Ebru; Ömercioğlu, Emel; Kılınç, Şeyma; Özmert, Elif Nursel (The Turkish Journal of Pediatrics, 2025)
Background. Autism spectrum disorder (ASD) is more frequently diagnosed in boys than in girls, possibly due to gender-based differences in symptom presentation or referral patterns. This study investigates gender-related variations in symptom severity and clinical presentation among preschool children referred for suspected ASD.Methods. This study included 125 children (boys: n=103; girls: n=22) aged 2–5 years suspected of having ASD. The Childhood Autism Rating Scale (CARS) was used to evaluate autism-related symptoms, focusing on presenting complaints and gender-specific differences in nonverbal communication and social interaction.Results. Girls had a significantly younger median age at assessment (28 months) compared to boys (33 months, p=0.03). In the minimal to no symptoms group, girls had significantly higher total CARS scores (median 26 vs. 22.5, p < 0.001) and elevated ratings in domains such as nonverbal communication (p=0.03), relationship to people (p=0.01), imitation (p < 0.001), and visual response (p < 0.001). In the severe group, girls also showed significantly higher scores in adaptation to change, taste, smel, and touch response and use, and fear or nervousness. Effect sizes ranged from small to strong. A negative correlation was found between assessment age and total CARS score (r= –0.45, p < 0.01), particularly among girls.Conclusion. This study highlights that girls may exhibit more prominent symptoms by the time they are referred for clinical evaluation, raising concerns about missed or delayed recognition of milder symptom profiles.
Keywords: autism spectrum disorder; sex characteristics; female; child; preschool; diagnosis